Interaction between the α-glucosidases, sucrase-isomaltase and maltase-glucoamylase, in human intestinal brush border membranes and its potential impact on disaccharide digestion - Tannous, Stephanie; Stellbrinck, Tammy; Hoter, Abdullah; Naim, Hassan Y. (Frontiers in Molecular Biosciences, 2023)
The two major intestinal α-glycosidases, sucrase-isomaltase (SI) and maltase-glucoamylase (MGAM), are active towards α-1,4 glycosidic linkages that prevail in starch. These enzymes share striking structural similarities and follow similar biosynthetic pathways. It has been hypothesized that starch digestion can be modulated via “toggling” of activities of these mucosal α-glycosidases, suggesting a possible interaction between these two enzyme complexes in the intestinal brush border membrane (BBM). Here, the potential interaction between SI and MGAM was investigated in solubilized BBMs utilizing reciprocal pull down assays, i.e., immunoprecipitation with anti-SI antibody followed by Western blotting with anti-MGAM antibody and vice versa. Our results demonstrate that SI interacts avidly with MGAM concomitant with a hetero-complex assembly in the BBMs. This interaction is resistant to detergents, such as Triton X-100 or Triton X-100 in combination with sodium deoxycholate. By contrast, inclusion of sodium deoxycholate into the solubilization buffer reduces the enzymatic activities towards sucrose and maltose substantially, most likely due to alterations in the quaternary structure of either enzyme. In view of their interaction, SI and MGAM regulate the final steps in starch digestion in the intestine, whereby SI assumes the major role by virtue of its predominant expression in the intestinal BBMs, while MGAM acts in auxiliary supportive fashion. These findings will help understand the pathophysiology of carbohydrate malabsorption in functional gastrointestinal disorders, particularly in irritable bowel syndrome, in which gene variants of SI are implicated.